Investigating the Geotourism phenomena in eroded land of Iran, Qeshm Island - Yazdi, Abdollah; Dabiri, Rahim (Revista Publicando, 2018)
Qeshm Island is one of the most beautiful Islands in Iran which has gathered a worldly unique and precious collection due to its eroded phenomena (i.e. Chahkooh canyon, Stars Valley and Tang-e Ali Strait); valuable geological heritage (i.e. Namakdan Salt Dome the world’s largest salt cave and etc.) and cultural and historical diversities. This Island is of particular importance in national and international fora due to the aggregation of these attractions, being located in the strategic region of Persian Gulf, being the first geopark of Iran and the Middle East and being known as the eroded land, it also can be called the geotourism gateway of Iran. In this paper along with introducing the theoretical concepts, geographical and geological features; ecotourism and geotourism potentials of Island, the impact of erosion on the creation of amazing geosites were also studied in this Island and solutions were offered for the development of geotourism. The research method in this paper was descriptive - analytical and data collection was done through library research, field studies and satellite images.